"A case of vanishing bone disease complicated by chylothorax- diagnosis and treatment". Issue 6 (June 2022) - Suzuki, N; Cintra, FF; Cintra, ML; Maciel, MG; Amstalden, EMI; Teixeira, F; Kubba, F
Summary: A 16-year old girl with Gorham-Stout disease is presented. She had progressive replacement of the bones of her left arm and shoulder girdle by fibroadipose tissue and numerous proliferated, non-neoplastic, lymphatic channels. The clinico-pathologic features of this condition are discussed, as are its possible complications and available therapeutic modalities.